PERANCANGAN E-COMMERCE PERANGKAT ROUTER ACCESS POINT DENGAN METODE PERSONAL EXTREME PROGRAMMING (PXP) (STUDI KASUS : PT. GRAND PRINCIPAL MANDIRI): PERANCANGAN E-COMMERCE DENGAN METODE PXP (STUDI KASUS : PT. GRAND PRINCIPAL MANDIRI) - Maulana, Bayu Ari; Maulana Ardiansyah; Mochamad Adhari Adiguna (PT Triputra Sejahtera Prima, 2025)
The development of the internet and technology has driven business transformation towards digitalization, including through e-commerce. PT. Grand Principal Mandiri, which operates in IT cabling, data center, and security system sectors, faces challenges in optimizing the efficiency of router and access point sales, which have been conducted through the Purchase Order (PO) method via email. This system is considered ineffective, limiting market reach and hindering customers from accessing real-time product information. This study aims to design a web-based e-commerce system using the Personal Extreme Programming (PXP) method. The research results indicate that the designed e-commerce system can enhance sales efficiency, provide more detailed product information, and enable real-time sales and stock data management to support more effective customer decision-making.